The Facts of the Story in Afrah Al-Qubbah Novel by Naghuib Mahfouz (A Structuralism Study by Robert Stanton) - Miftahul Khasanah; Akmaliyah Akmaliyah; M. Rosyid Ridho (Universitas Muria Kudus, 2026)
This study is motivated by the importance of understanding literary works through their intrinsic structure, particularly in revealing how narrative elements construct meaning and social criticism. This study aims to analyze the factual elements of the story in the novel Afrah al Qubbah by Naghuib Mahfouz usin Robert Staton’s Structuralism approach. The focus of this study includes three intrinsic elements, namely characters, plot and setting. The method used is descriptive qualitative, with data collection techniques in the form of reading and note-taking of the novel text. The data source in this study is the novel Afrah al Qubbah, wich is analyzed based on the structural relationship among intrinsic elements. The result show that characters, plot and setting have structural interconnections that form a unifed story. Abbas, as the main character, becomes the center of conflict through the manuscript he writes, which reveals family realities and generates moral, emotional, and social tensions. The plot develops through the stage of exposition, complication, climax and resolution, which strengthen the tragic nuance of the story. The social, spatial, and temporal settings also support the development of conflict and reflect the breakdown of values in society. Overall, these theree elements construct meaning and present social criticism. The implications of this study indicate that structural analysis can enhance literary understanding, improve crictical reading skills and support literature learning.